Inmerso (2017)
"Nature is present in all parts and yet we fail to see it, we leave it aside, away from it and we rest the importance and relevance that nature actually has in our lives. The central theme of the research is the relationship between the human being and nature. What is the relation of the human being and nature? How do we relate to nature? Are we aware of the connections we have with it? I choose nature and the relationship it has with it as the theme based on the attraction I feel towards it, the need to portray it constantly and a call to feel it and perceive it in many ways. This is why the research process determines the relationship, the connections and the behaviors that exist between the human being and nature. In order to understand the bottom of the importance of being aware of the connection. -- Tomado del Formato de Documento de Grado.